Propiedades de las nominalizaciones de actividad y práctica - Fábregas, Antonio (Círculo de Lingüística Aplicada a la Comunicación, 2021)
The main goal of this article is to motivate the existence of a grammatically well-defined class of nominalisations expressing activities or practices, whose properties differentiate them froim event, quality or participant nominalisations. We will show that these nouns, deverbal or no, define different classes of general eventualities that are not ijnstantiated in specific time periods or points, and display a semantic, syntactic and morphological behaviour that justify their inclusion in the taxonomy of nominalisations, as a separate class. We will argue that these structures come from bases that, independently of the input category, lack the capacity to denote specific tokens of an eventuality, and because of that are used to define jobs, hobbies and other activities that are characteristic of people or objects, unrelated to temporal parameters.